Leveraging Edge Computing for IPTV Optimisation in 5G Networks: A Comprehensive Analysis of Performance and Scalability - Prodani, Fatmira; Gjermeni, Frida; Rista, Amarildo (Statistics, Optimization & Information Computing, 2026)
This paper addressed the integration of edge computing into the infrastructure of fifth-generation (5G) networks as a key approach to ensuring high performance, scalability, quality of service of Internet Protocol Television (IPTV) services. The research methodology was based on a comparative analysis of architectures, streaming characteristics, performance parameters, system reactions as the number of users increases. The paper summarised advanced methods for optimising Internet Protocol Television based on edge computing, including local caching, adaptive transmission, load balancing, traffic routing. The integration of edge computing with 5G creates a solid technological foundation for building modern Internet Protocol Television systems capable of meeting the growing needs of users and providing a high level of content quality even under high network load conditions.